Balancing National Constitutions and International Trade Commitments: Comparative Insights from Indonesia, Thailand, and India - Hananto Widodo; Intan Lovisonnya; Fradhana Putra Disantara; Ruetaitip Chansrakaeo; Uzodinma Yurriens Ezenduka (Faculty of Law Universitas Lampung, 2025)
Economic globalization has heightened tensions between national sovereignty and international trade obligations. This study compares constitutional review mechanisms in Indonesia, Thailand, and India, representing civil law and common law systems. Using normative legal methods with statute and comparative analysis, it finds that Indonesia applies ex post review of ratification laws, Thailand uses preventive ex ante review, and India employs substantive, precedent-based judicial review. Effectiveness varies: India achieves high substantive effectiveness through judicial activism, Thailand excels procedurally, and Indonesia remains limited to formal review. The study concludes that constitutional review effectiveness depends on institutional design, legal tradition, and the ability to balance constitutional supremacy with international commitments.